Noncollagen Dermal Fillers: A Summary of the Clinical Trials Used for Their FDA Approval. Issue 12 (December 2019) - Jiang, Betty; Ramirez, Mary; Ranjit-Reeves, Roshni; Baumann, Leslie; Woodward, Julie
Abstract : BACKGROUND: Many noncollagen dermal fillers (NCDFs) have been approved by the FDA and are currently the second-most performed noninvasive cosmetic procedure. OBJECTIVE: To summarize and compare the clinical trials reviewed by the United States FDA in the approval of NCDFs. METHODS: The FDA Premarket Approval (PMA) site was queried, and the year of approval, indication, design, primary end points, touch-ups, retreatments, and study duration were extracted and tabulated. RESULTS: Twenty-one FDA-approved NCDFs from 2003 to 2018 and 24 Summary of Safety and Effectiveness documents were reviewed. Differences in the trial design and in reporting of data make comparisons difficult. This article provides comparative tables to make interpreting the various trial results more straightforward. Limitations: Primary efficacy end points and the way that filler volumes were reported varied by company. This article does not focus on secondary end points or safety data. CONCLUSION: A comprehensive and comparative review of clinical trials of NCDFs by the FDA demonstrates that differences in data reporting, especially for touch-ups and retreatments, make filler duration difficult to compare and interpret. Understanding of the trial design will allow the clinician to become more astute and allow for better management of patient expectations in clinical practice.